Assessment of the effectiveness of the mentorship programme in land reform : a case of land restitution in Sekhukhune District, Limpopo Province - Golele, Nyiko Shadrack (University of Limpopo, 2016)
In South Africa, the Land Reform Programme is a priority programme aimed to address land ownership through land redistribution and restitution programmes. The aim of this study was to assess the effectiveness of the mentorship programme in land reform programme. The study adopted a qualitative approach in which one mentor, three executive committee members, 20 protégé's (new farmers) and a manager from the Department of Rural Development and Land Reform were interviewed. The findings show that there are essential qualities and characteristics that a mentor and Protégé should possess to ensure a successful mentorship programme. The qualities linked to a mentor include a good commended, traceable track record; he/she must be people’s person (that is, he/she must be able to get along with people); a motivator to other people; he/she must be able to make people productive and take firm decisions; and must be a knowledgeable, respectful and trustworthy person. The ‘ideal’ protégé should be honest, committed, respectful and hard working. The characteristics of a mentee include honesty, passionate with farming and reliability. All these qualities must be undergirded by a good mentorship relationship between a mentor and mentee, a condition which is crucial for success. The study also found out that a lack of respect from either the mentor or mentee, a lack of willingness to cooperate, a lack of commitment have the potential to lead to negative impact on the mentorship programme and affects farm production. Due to the fact that the mentorship programme applies a participatory approach, beneficiaries are at liberty to select their own mentor. They also have the opportunity to make input when a land use plan and a business plan are developed. Key words: Mentorship; beneficiary, land reform; agriculture; business plan; sustainability and recapitalisation.
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Mentorship; Land reform; Agriculture; Business plan; Sustainability; Recapitalisation; Land reform -- South Africa